1997
DOI: 10.3758/bf03209401
|View full text |Cite
|
Sign up to set email alerts
|

Shape equivalence under perspective and projective transformations

Abstract: When a planar shape is viewed obliquely, it is deformed by a perspective deformation. If the visual system were to pick up geometrical invariants from such projections, these would necessarily be invariant under the wider class of projective transformations. Towhat extent can the visual system tell the difference between perspective and nonperspective but still projective deformations of shapes? To investigate this, observers were asked to indicate which of two test patterns most resembled a standard pattern. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 23 publications
(7 reference statements)
0
19
0
Order By: Relevance
“…Even so, it is evident that an invariants-based approach can be useful, and its geometric foundations can lead to predictions that are testable and relevant. Thus, the idea of minimal information is based on a hierarchy of transformation geometries (which has found application in other contexts; e.g., Tittle, Todd, Perotti, & Norman, 1995), and this framework allows one to derive predictions about shape equivalence under different sets of transformations (e.g., perspective versus projective; Wagemans, Lamote, & Van Gool, 1997;also Foster, 1975).…”
Section: Mental Transformations Versus Invariantsmentioning
confidence: 99%
“…Even so, it is evident that an invariants-based approach can be useful, and its geometric foundations can lead to predictions that are testable and relevant. Thus, the idea of minimal information is based on a hierarchy of transformation geometries (which has found application in other contexts; e.g., Tittle, Todd, Perotti, & Norman, 1995), and this framework allows one to derive predictions about shape equivalence under different sets of transformations (e.g., perspective versus projective; Wagemans, Lamote, & Van Gool, 1997;also Foster, 1975).…”
Section: Mental Transformations Versus Invariantsmentioning
confidence: 99%
“…In our present experimental procedure, a standard form was presented together with a rotatedÂreflected image of the standard form, and the subject was required to respond to the sameÂdifferent object by an appropriate key-press. In contrast to this type of discrimination procedure was the three-pattern configuration procedure used by Wagemans et al (1997). They used two patterns below the standard pattern, and these two patterns were images of the standard form by perspective or projective transformations or of a new pseudo-random pattern.…”
Section: Remarks On Ecological Relevancementioning
confidence: 99%
“…However, Wagemans et al (1997) prefer to attribute their results to quantitative parametric differences rather than the fundamental qualitative difference between perspective and projective transformations. Another conclusion of their study shows that although compactness varies with parameter values, the observer's decision cannot be determined by a simple preference for similar compactness in shapes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wagemans, Lamote and van Gool [22] compared the perceived resemblance of "projectively equivalent" pairs of figures with that of more specific "perspectively equivalent" pairs of figures. The results showed that people judged both types of pairs as identical, although there was a preference toward equivalent pairs after perspective transformation compared to equivalent pairs after projective transformation.…”
Section: Introductionmentioning
confidence: 99%